The abolition of prison - Lesage de La Haye, Jacques (AK Press, 2021)
Why prisons? --The revolt of abolitionists --What prison is like --Sex and prison --No integration, no re-entry --Alternatives to incarceration: the forerunners --Recent and current alternatives to incarceration --Mediation and reparation --How do we go abolition? --Why abolition?